Common and Specific Features of Migration Flows in Russia, CIS and Far Abroad - Kuprina, Tamara Vladimirovna; Sandler, Margarita (Economy of Regions, 2015)
The article discusses the features of migration flows in Russia, CIS and abroad in terms of transnationality and translocality. Special attention is paid to migration flows from Asia, depending on the gender perception. During the analysis, the preferences of migrants of different age groups are determined. It shows their desire for a more independent financial and professional life, relationship with family responsibilities, plans for the future. The data obtained by the method of continuous selection have led to the following conclusions: migration is a multidimensional phenomenon that requires multidisciplinary research; the heterogeneity of migration flows to the socio-cultural and gender features must be taken into account; the problem of illegal migration requires special solutions; in connection with the emigration of highly skilled professionals and immigration of low-skilled personnel, a professional important indicator of migratory replacement and attracting compatriots from abroad are important. The data obtained can be used for ethnic and cultural planning in order to improve production activities that affect the quality of solving of production tasks and programming adaptation of migrants as the significant impact of intangible factors on the development of society has been noted by economists for a long time. Thus, the economic sustainability requires new thinking based on socio-cultural sustainability determined by such global phenomena as international migration flows.